ALTERNATIF INDEKS GIZI SEIMBANG UNTUK PENILAIAN MUTU GIZI KONSUMSI PANGAN PRIA DEWASA INDONESIA - Atika Primadala Amrin; Hardinsyah Hardinsyah; Cesilia Meti Dwiriani (Jurnal Gizi dan Pangan, 2013)
The study was aimed to develop Balanced Diet Index (BDI) for Indonesian adult males. The spesific purposes of this study were to assess food consumption pattern of Indonesian adult males, to develop several alternatives of BDIs and to select the most appropriate BDI for Indonesian adult males. The design of the study was cross-sectional, using the food consumption data from Basic Health Research 2010 collected using 24-hours recall method. The data covered 64 448 subjects, and 61 129 of them were analyzed in this study. There were 10 alternatives of BDIs developed based on the food group and their intake, and also their scoring systems. The gold standard used to validate the BDI is the mean adequacy ratio (MAR) measured by mean nutrient adequacy of 16 nutrients. The result showed the pearson correlation coefficient of the BDI and MAR range from 0.46 to 0.64. The most appropriate BDI to determine MAR is BDI3-60 (r=0.64). BDI3-60 consists of six food and implementing 3-level of scoring system.